2016
DOI: 10.1007/s12035-016-9711-y
|View full text |Cite
|
Sign up to set email alerts
|

Klotho Gene and Selective Serotonin Reuptake Inhibitors: Response to Treatment in Late-Life Major Depressive Disorder

Abstract: Klotho protein, encoded by the Klotho gene (KL) at locus 13q12, is an antiaging hormone-like protein playing a pivotal role in cell metabolism homeostasis and associated to longevity and age-related diseases. In particular, altered cell metabolism in central nervous system may influence the behavior of serotoninergic neurons. The role of KL in the response to treatment with selective serotonin reuptake inhibitors (SSRIs) in late-life depressive syndromes and late-life major depressive disorder (MDD) is unclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 88 publications
1
14
0
1
Order By: Relevance
“…In addition, we observed that Klt and 25(OH)D are statistically significant correlated with NMS burdens of mood in MSA patients (Table ). Specifically, Klt and 25(OH)D have a negative association with mood and attention/memory, and a positive correlation with MMSE in MSA patients, further indicating that mood and attention/memory disorders may be targets for assessment by serum levels of Klt and 25(OH)D. In agreement with our notions, several studies have also reported that Klt deficiency and a low level of 25(OH)D was associated with mood, memory deterioration, and cognitive dysfunction . Consistent with previous reports, we also found that plasma levels of Klt have a significant negative correlation with the cardiovascular and urinary domains in MSA patients.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we observed that Klt and 25(OH)D are statistically significant correlated with NMS burdens of mood in MSA patients (Table ). Specifically, Klt and 25(OH)D have a negative association with mood and attention/memory, and a positive correlation with MMSE in MSA patients, further indicating that mood and attention/memory disorders may be targets for assessment by serum levels of Klt and 25(OH)D. In agreement with our notions, several studies have also reported that Klt deficiency and a low level of 25(OH)D was associated with mood, memory deterioration, and cognitive dysfunction . Consistent with previous reports, we also found that plasma levels of Klt have a significant negative correlation with the cardiovascular and urinary domains in MSA patients.…”
Section: Discussionsupporting
confidence: 92%
“…The levels of Klotho protein having sialidase activity are known to increase after electroconvulsive therapy (24) in the spinal fluid of elderly patients with depression. In addition, a Klotho gene single nucleotide polymorphism (SNP) is reported to be associated with antidepressant response in elderly patients with depression(25). Together, the binding of sialic acid-specific lectins above we showed could be used as a marker of treatment response.…”
mentioning
confidence: 66%
“…Crucially, we demonstrated cross‐trial replication of prediction performance across rating scales in both STAR*D (QIDS‐C scale) and ISPC (HDRS scale) trials with precision similar to that observed in training with PGRN‐AMPS data. This work also represents an advance over traditional pharmacogenetic candidate gene approaches that identify plausible genes and SNPs associated with outcomes . We achieved that advance by asking whether the application of machine‐learning approaches that combine clinical assessments with a group of functionally validated pharmacogenomic SNPs as predictor variables might make it possible to predict SSRI treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This work also represents an advance over traditional pharmacogenetic candidate gene approaches that identify plausible genes and SNPs associated with outcomes. [28][29][30][31][32][33][34] We achieved that advance by asking whether the application of machine-learning approaches that combine clinical assessments with a group of functionally validated pharmacogenomic SNPs as predictor variables might make it possible to predict SSRI treatment outcomes. Taken as a whole, our findings represent an important step toward the goal of algorithmically determining whether SSRIs are likely to be effective in patients with MDD prior to treatment initiation.…”
Section: Improved Predictions and Mechanistic Significancementioning
confidence: 99%